BALANCE DENSITY AND PRIVACY: DESIGNING EFFICIENT CO-WORKING SPACE IN LAHORE (A STUDY OF CO WORKING SPACES, LAHORE) - Syed Zoraiz Ahmed Subhani; Umer Mahboob Malik; Mahrukh Khalid; Maryam Jaseem (Policy Journal of Social Science Review, 2026)
The need of flexible workplaces is among the elements that contributes significantly to the growing popularity of co working among freelancers, entrepreneurs, remote working. This setup is also supported by development of technologies, new organizational structure, and work methods during recent pandemic time. Being widely adopted now a days, most co-working spaces still face a range of challenges like density in privacy and acoustic problem. In addition, over population, noise, lack of personalized space and insufficient negative effect user experience and productivity in the setting. The use of the quantitative research method through a systematic literature review and bibliometric analysis in the attempt to explore the new trends and approaches to design of co working environments. Data collection was done using peer reviewed jounal articles, conference paper, and google scholar etc. the use of bibliometric techniques helped in conducting thematic mapping, citation analysis, co-occurrence analysis, and keyword analysis to reveal the patterns, themes, and knowledge gaps existing studies. It appears that users have shown great preference for flexible space environment that provides for efficient collaboration and personal concentration. Although the open plan design provides opportunity for communication and knowledge sharing. It has been associated with problems relating to privacy invasion, distractions, and poor acoustic, and decreased productivity. Additionally, it become evident that effect spatial zoning, acoustic treatment, use of modular furniture system, adaptability and multifunctionality can directly enhance satisfaction levels, workplace efficiency and performance. The need for designing flexible workplaces that provide adequate opportunities for privacy, collaboration and other user requirements. Keywords: Space Effectiveness, Space Planning in the Workplace, User Satisfaction, Space Planning.